Implementasi Kurikulum Pondok Pesantren Saengthip Wittaya Shcoll Yala Thailand Selatan - Maha, Nadia; Arifmiboy, Arifmiboy; M, Iswantir; Wati, Salmi (Lembaga Yasin AlSys, 2023)
The author's reason for choosing this title is to find out the implementation of the curriculum for the Saengthip Wittaya Islamic boarding school which has become a phenomenon in the world of education so that at the age of its founding which is still new it can attract public interest to prepare their children to go to school at Saengthip Wittaya. However, there are students who have difficulty understanding the words in the book, which are difficult to understand. So the authors are interested in researching the implementation of the study of the yellow book at the Saenghtip Witaya Islamic boarding school.This study uses a qualitative approach. The key informants are babo/kiai. The techniques used in research are data collection techniques, field observations, interviews, and documentation. As for the analysis, the writer uses descriptive analysis which aims to explain or describe the research data in the form of words. The results of the study show that the implementation of learning the Muhimmah Book at Saengthip Wittaya is that the implementation given or conveyed by the kiai/babo is already good, the aim is so that students can promote benefits in activities in daily life and benefits for the future. The methods used are many but focus on the lecture method, and the question and answer method. There is a lot of material used but it focuses on praising husbands for wives, various accidents of wives for husbands, punishments in the grave. And the obstacles in implementation are that students do not understand in learning, not getting used to reading sentences in other languages, if we read often, the reading will be good and we can read other books.